2007
DOI: 10.1097/cmr.0b013e3282f1d2d9
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel node-guided evaluation of drainage patterns for melanoma of the helix of the ear

Abstract: The head and neck region, and especially the ear and its helix, is notorious for its ambiguous pattern of lymphatic drainage. Therefore, the primary nodal drainage basins in melanoma of the helix of the ear are often unpredictable. The aim of the study was to examine the value of sentinel lymph node biopsy in melanoma of the helix of the ear and to describe the natural history of the disease. Fifteen consecutive patients (14 men) with primary melanoma of the helix of the ear (median thickness, 1.2 mm; range, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Particularly, total or partial amputation of the ear could render a patient unable to wear eye glasses or some hearing aids. These aggressive recommendations dominated the literature for over a decade until larger series were reported [18,19]. Recent studies, have demonstrated that these melanomas can be treated conservatively avoiding aggressive amputations and advocating more moderate treatment strategies including Mohs surgery, composite "wedge" excision of skin and cartilage-sparing surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, total or partial amputation of the ear could render a patient unable to wear eye glasses or some hearing aids. These aggressive recommendations dominated the literature for over a decade until larger series were reported [18,19]. Recent studies, have demonstrated that these melanomas can be treated conservatively avoiding aggressive amputations and advocating more moderate treatment strategies including Mohs surgery, composite "wedge" excision of skin and cartilage-sparing surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite the great variability, identification of the SLN is possible in >90% of cases. 9,20,29 All the studies reported a predominance of drainage at level II, and Shpitzer et al 9 always found at least one SLN at levels II or III in 15 melanomas of the helix 9 ( Table 1).…”
Section: In 2001mentioning
confidence: 95%
“…Several authors support the idea that these patterns are highly unpredictable, 4,6,14,15,20,21,25,27,29 but only a few studies focus on the lymphoscintigraphy and the drainage patterns of the external ear. Nine studies report information about the regional lymph nodes, 4,6,9,14,16,20,24,25,29 but only four of them describe the exact location of the identified sentinel node according to Robbins' topographic classification 31 of the cervical node levels. 6,9,14,16 These studies confirm that the drainage pattern of the external ear is variable and unpredictable; in Peach et al's series of 111 lymphoscintigraphy, lymphatic drainage occurred in a retrograde, antegrade, or transaural pattern, although never contralaterally.…”
Section: In 2001mentioning
confidence: 99%
See 2 more Smart Citations